The influence of untreated sugarcane bagasse ash on the microstructural and mechanical properties of mortars - Maldonado García, M. A.; Hernández Toledo, U. I.; Montes García, P.; Valdez Tamez, Pedro Leobardo (Instituto de Ciencias de la Construcción Eduardo Torroja, 2018)
ABSTRACT: This study investigated the effects of the addition of untreated sugarcane bagasse ash (UtSCBA) on the microstructural and mechanical properties of mortars. The SCBA was sieved for only five minutes through a No. 200 ASTM mesh, and fully characterized by chemical composition analysis, laser ray diffraction, the physical absorption of gas, scanning electron microscopy (SEM) and X-ray diffraction (XRD) techniques. Mortar mixtures with 0, 10 and 20% UtSCBA as cement replacement and a constant 0.63 water/cementitious material ratio were prepared. Fresh properties of the mortars were obtained. The microstructural characteristics of the mortars at 1, 7, 28, 90 and 600 days were evaluated by SEM and XRD. The compressive strengths of the mortars at the same ages were then obtained. The results show that the addition of 10 and 20% UtSCBA caused a slight decrease in workability of the mortars but improved their microstructure, increasing the long-term compressive strength. Keywords: Pozzolan, waste treatment, mortar, hydration products, compressive strength